VULNERACIÓN DE LA PROPORCIONALIDAD FRENTE AL ARTÍCULO DE MUERTE POR ACCIDENTE DE TRÁNSITO EN ESTADO DE EBRIEDAD Y EL HOMICIDIO, ANÁLISIS DE DOLÓ Y CULPA - Maza Burneo, Paula Patricia (2024)
The present Qualification Work called: “VULNERATION OF PROPORTIONALITY AGAINST THE ARTICLE OF DEATH BY TRAFFIC ACCIDENT IN A STATE OF DRUNK AND HOMICIDE, ANALYSIS OF DOLÓ AND GUILT”, has as its primary objective to analyze the violation of proportionality against the article of death due to traffic accident while intoxicated and homicide, in which an analysis of intent and guilt was carried out. The purpose of this investigation is to legally argue the solution to the problem posed: In what type of trials can proportionality be violated in cases of death due to a traffic accident while intoxicated and homicide? For which a qualitative, descriptive and empirical research was carried out, in which the non-probabilistic convenience sampling technique was used to establish the study sample; The study sample was 4 lawyers to whom a previously designed interview was applied and 22 natural persons to whom a survey was applied about knowledge about the legislation related to death due to traffic accidents.